Newborn Boys and Girls Differ in the Lipid Composition of Vernix Caseosa - Míková, Radka; Vrkoslav, Vladimír; Hanus, Robert; Háková, Eva; Hábová, Zuzana; Doležal, Antonín; Plavka, Richard; Coufal, Pavel; Cvačka, Josef (PLOS ONE, 2014)
Vernix caseosa protects the skin of a human fetus during the last trimester of pregnancy and of a newborn after the delivery. Besides its cellular and proteinaceous components, an important constituent and functional agent is a complex lipid fraction, implicated in a multitude of salubrious effects of vernix caseosa. Little is known about how the chemical composition of vernix caseosa lipids is affected by various biological characteristics of the baby, such as the gestational age, birth weight, and, last but not least, the gender of the newborn. This study reports on the chemical variability of lipids contained in the vernix caseosa of twenty newborn girls and boys and shows that the quantitative patterns of the lipids are sex-specific. The specificity of lipids was investigated at the level of fatty acids in the total lipid extracts and intact lipids of several neutral lipid classes. Hydrocarbons, wax esters, cholesteryl esters, diol diesters and triacylglycerols were isolated using optimized semipreparative thin-layer chromatography, and the molecular species within each class were characterized using matrix-assisted laser desorption/ionization mass spectrometry. Statistical evaluation revealed significant quantitative sex-related differences in the lipid composition of vernix caseosa among the newborns, pronounced in the two lipid classes associated with the activity of sebaceous glands. Higher proportions of wax esters and triacylglycerols with longer hydrocarbon chains were observed in newborn girls.